An Immunological Perspective to Non-syndromic Sensorineural Hearing Loss - Sindura, K. P.; Banerjee, Moinak (Frontiers in Immunology, 2019)
Conventionally the etiology of congenital Non-Syndromic Hearing Loss has been attributed to mutations in the genes involved in ion homeostasis or the structural compartments of the inner ear. However, this contributes to only a part of the problem, as still the determinants for a large majority of the Non- Syndromic Hearing loss seems to be an enigma. Evidences indicate that pathogens like Rubella, Cytomegalovirus and many other infections can also result in congenital hearing loss. Additionally, there are variety of factors other than the viral mediators, that can act as stressors to trigger an altered immune response, during the gestational period of the mother. It is also known that nonspecific stimulation of the immune system can mimic an infection status. This indicates a strong role for environmental factors towards their contribution to the pathology, possibly by influencing the host immune response. These varieties of known or unknown environmental factors interact with the susceptible variants in immune response genes in defining the threshold for protection or infection in an individual. Considering this background we propose to present this perspective that threshold of the host immune response during the prenatal conditions, in response to environmental stimulus, might be determined by the susceptible variants in immune response genes. This in turn can directly or indirectly influence the genes involved in maintaining the structural components or ion homeostasis, resulting in hearing loss. The threshold of immune response alterations may be heavily dependent on the immunogenetic profile of the mother or the fetus.